Mathematical modeling of the oxygen storage capacity phenomenon studied by CO pulse transient experiments over Pd/CeO2 catalyst - Costa, Costas; Christou, Stavroula Y.; Georgiou, Georgios C.; Efstathiou, A. M. (My University, 2003)
A mathematical model has been developed for the first time to study the oxygen storage capacity (OSC) phenomenon by the CO pulse injection technique over a 1 wt% Pd/CeO2 model catalyst in the 500-700°C range. A two-step reaction path that involves the reaction of gaseous CO with the oxygen species of PdO (pre-oxidized supported palladium particles in the 500-700°C range) and of the back-spillover of the oxygen process from ceria to the oxygen vacant sites of surface PdO has been proven to better describe the outlet CO pulse transient response and the experimentally measured quantity of OSC (μatoms of O/g) obtained in a CSTR microreactor. With the proposed mathematical model, the transient rates of the CO oxidation reaction and of the back-spillover of the oxygen process can be calculated. In the 500-700°C range, the transient rate of CO oxidation was always greater than that of the back-spillover of oxygen. The ratio, ρ, of the maximum CO oxidation rate to the maximum back-spillover of the oxygen rate was found to decrease with increasing reaction temperature in the 500-700°C range. In particular, at 500 and 700°C the value of ρ was found to be 1.6 and 1.2, respectively. The present mathematical model allows also the calculation of the intrinsic rate constant k1 (s-1) of the Eley-Rideal step for the reaction of gaseous CO with surface oxygen species of PdO to form CO 2. An activation energy of 9.2 kJ/mol was estimated for this reaction step. In addition, an apparent rate constant k2 app (s-1) was estimated for the process of back-spillover of oxygen. The ratio of the two rate constants (k1/k2 app) was found to be greater than 100 in the 500-700°C range. A Langmuir-Hinshelwood surface elementary reaction step of adsorbed CO with atomic oxygen of PdO failed to describe the experimental transient kinetics of CO oxidation in the 500-700°C range. The results of the present work provide the means for a better understanding of the effects of various additives and contaminants present in a three-way commercial catalytic converter and other related model catalysts on their OSC kinetic behavior. In addition, intrinsic effects of a given regeneration method for a commercial three-way catalyst on the OSC phenomenon could better be studied by making use of the results of the present mathematical model.
Keywords: Mathematical modeling of OSC; Oxygen storage capacity; Pulse CO oxidation; Supported-Pd; Three-way catalysts; Transient CO oxidation